PENGARUH MEDIA INFOKUS TERHADAP MOTIVASI SISWA KELAS V ( LIMA ) DALAM MATA PELAJARAN PAI DI SD NEGERI 007 SUNGAI KUNING KECAMATAN SINGINGI - Ariyanto Ariyanto (Universitas Islam Kuantan Singingi, 2020)
This study aims to determine the effect of the use of infocus media on the motivation of fifth grade students at SDN 007 Sungai Kuning Singingi Kuantan Singingi District. This type of quantitative descriptive study uses a Likert Scale approach as a method of data collection. The results of the study show that the calculated r value of 0.428 is above the significant r table, namely at a significant level of 1% at 0.3233 and at a significant level of 5% at 0, 3809. On this basis it shows that there is a relationship between the use of infocus media on the motivation of fifth grade students in PAI learning at SD7 007 Sungai Kuning District Singingi, Kuantan Singingi District.